Literatur Review: Mengapa Rekam Medis Tidak Lengkap? - Sri Sugiarsi; Rohmadi Rohmadi (Indonesian of Health Information Management Journal (INOHIM), 2020)
AbstractMedical records are a source of important medical data and information to present a patient's medical history and status, therefore medical records must be complete. However, incomplete medical records were still found. The purpose of this study was to find the causes of incomplete medical records. This study uses a literature review approach with the PICO framework. Literature search using the Google Scholar database. The keywords and Boolean operators used in this study are "medical records" AND completeness of OR quantitative analysis. The inclusion criteria were inpatient medical records, research journals published in 2017 - 2020, in Indonesian language, research design; quantitative and qualitative, the indicators used are completeness, causal factors. And as an exclusion criterion, articles are incomplete and cannot be downloaded. The results of the study found that the model causes the medical record to be incomplete; where the dominant factor is the doctor, and the second factor is the medical record form design. Followed by the next factor is a method in the form of policy and SOP, a mechanism in the form of a structured monitoring & evaluation system. The conclusion of this study is doctors and form design as the most dominant cause of incomplete medical records.Keywords: literature review, PICO, medical record, incompleteAbstrakRekam medis merupakan sumber data dan informasi medis yang penting untuk menyajikan riwayat medis dan status pasien, oleh karena itu rekam medis harus lengkap dan benar. Namun demikian masih ditemukan catatan medis yang tidak lengkap dan tidak benar. Penelitian ini bertujuan untuk menemukan penyebab rekam medis tidak lengkap. Penelitian ini menggunakan pendekatan literature review dengan framework PICO. Pencarian artikel menggunakan database Google Scholar. Keyword dan Boolean operator dalam penelitian ini adalah “rekam medis” AND kelengkapan OR analisis kuantitatif. Kriteria inklusi adalah rekam medis rawat inap, jurnal penelitian yang dipublikasikan tahun 2017 – 2020, berbahasa Indonesia, rancangan penelitian; kuantitatif dan kualitatif, indikator yang digunakan kelengkapan, faktor penyebab. Dan sebagai kriteria eksklusinya adalah artikel tidak lengkap dan tidak bisa  diunduh. Hasil penelitian ditemukan model penyebab rekam medis tidak lengkap; dimana faktor dominan adalah dokter, dan sebagai faktor kedua adalah desain formulir rekam medis. Disusul faktor berikutnya adalah metode berupa kebijakan dan standard operating procedure, machine berupa sistem monitoring & evaluasi yang terstruktur. Simpulan penelitian ini adalah dokter dan desain formulir sebagai faktor penyebab paling dominan rekam medis tidak lengkap.Kata Kunci: literatur review, PICO, rekam medis, tidak lengkap